2019
DOI: 10.1371/journal.pone.0225479
|View full text |Cite
|
Sign up to set email alerts
|

The majority of skin lesions in pediatric primary care attention could be managed by Teledermatology

Abstract: BackgroundTeledermatology is a tool that provides accurate diagnosis and has been gaining more emphasis over time. It can be used for triage in primary care attention to address skin conditions improving access and reducing time to treatment for surgical, severe or even lethal diseases.ObjectivesOur main goal was to evaluate the proportion of pediatric patient’s lesions that could be managed using teledermatology in primary care attention. Secondly, we wanted to assess the ten most frequent skin conditions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
2
17
2
4
Order By: Relevance
“…Up to one‐third of patients with neoplasms required an in‐person visit, while none of the patients with acne, dermatophyte or ectoparasitic infections had to be seen in person. Previous studies have also reported conditions such as acne, atopic dermatitis, seborrheic dermatitis, xerosis and dermatophytosis to be particularly suited for telemedicine 12–14 . Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Up to one‐third of patients with neoplasms required an in‐person visit, while none of the patients with acne, dermatophyte or ectoparasitic infections had to be seen in person. Previous studies have also reported conditions such as acne, atopic dermatitis, seborrheic dermatitis, xerosis and dermatophytosis to be particularly suited for telemedicine 12–14 . Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced cell-phone camera technology has made it easy for taking and sending quality photographs. Studies have demonstrated that most skin lesions in pediatric primary care attention could be managed by tele-dermatology (31,32).…”
Section: Discussionmentioning
confidence: 99%
“… 11 Previously, we showed that telemedicine was efficient for triage and management of dermatoses in the pediatric age group. 12 In the present study, the majority of patients with atopic dermatitis did not require an in-person visit with the dermatologist or allergist (72%), presumably because they had mild disease. Patients with more severe atopic dermatitis were probably sent for in-person appointments (28%).…”
Section: Discussionmentioning
confidence: 51%